Unleashing the Power of Biologics: Exploring the Governance and Regulation of Membrane-Based Virus Purification (MVP) Technologies - Ben Galloway; Patrick A. Stewart; Camille Gilmore; Victor Akakpo; Nataliia Borozdina; Geoboo Song; Sumith Ranil Wickramasinghe; Xianghong Qian; Asingsa Lakmini Weerasinghe Wickramasinghe Arachchige; Sarah W. Harcum (Biologics, 2025)
Background: Biologics is an exciting and growing area of medicine. Within the larger field of biologics, the use of viral vectors and virus-like particles (VLPs) is increasingly common, making it crucial to develop innovative and practical unit operations for the related purification process. Objective: Some scientists and engineers propose that membrane-based downstream virus purification (MVP) platforms would allow for more scalable and cost-effective production of these critical particles. However, the so-cial, political, and ethical implications of these advancements remain largely unex-plored. This paper aims to explore various pivotal facets of MVP technology govern-ance and regulations within the U.S. context, including (1) government policy ar-rangements related to the implementation of the technologies, (2) stakeholder atti-tudes, policy preferences, and behaviors, and (3) the fundamental factors that shape these attitudes, policy preferences, and behaviors. Methods: In doing so, we analyze publicly available federal and state government documents pertaining to biomanu-facturing, healthcare, and legislative attempts. Additionally, we will perform a stake-holder analysis on relevant industries, healthcare service providers, and recipients. Conclusions: Our goal is to outline the socio-political, ethical, and regulatory factors pertaining to the regulation and governance of these technologies.